On gauge invariance and ward identities for the Wilsonian tenormalisation group - Litim, Daniel F.; Pawlowski, Jan M. (Arxiv, 1998)
We investigate non-Abelian gauge theories within a Wilsonian Renormalisation Group approach. The cut-off term inherent in this approach leads to a modified Ward identity (mWI). It is shown that this mWI is compatible with the flow and that the full effective action satisfies the usual Ward identity (WI). The universal 1-loop beta-function is derived within this approach and the extension to the 2-loop level is briefly outlined.